1998
DOI: 10.1105/tpc.10.5.685
|View full text |Cite
|
Sign up to set email alerts
|

Barley Aleurone Cells Contain Two Types of Vacuoles: Characterization of Lytic Organelles by Use of Fluorescent Probes

Abstract: Light microscopy was used to study the structure and function of vacuoles in living protoplasts of barley ( Hordeum vulgare cv Himalaya) aleurone. Light microscopy showed that aleurone protoplasts contain two distinct types of vacuole: the protein storage vacuole and a lysosome-like organelle, which we have called the secondary vacuole. Fluorescence microscopy using pH-sensitive fluorescent probes and a fluorogenic substrate for cysteine proteases showed that both protein storage vacuoles and secondary vacuole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(52 citation statements)
references
References 54 publications
1
50
0
1
Order By: Relevance
“…The presence of both lytic (<10 μm) and protein storage compartment (>10 μm) vacuole types was confirmed in barley aleurone cells by light and fluorescence microscopy studies (Swanson et al , 1998). In wheat, the PSVs are composed only of a protein matrix and globoids with phytic acid mineral salts (Morrison et al , 1975).…”
Section: Introductionmentioning
confidence: 89%
“…The presence of both lytic (<10 μm) and protein storage compartment (>10 μm) vacuole types was confirmed in barley aleurone cells by light and fluorescence microscopy studies (Swanson et al , 1998). In wheat, the PSVs are composed only of a protein matrix and globoids with phytic acid mineral salts (Morrison et al , 1975).…”
Section: Introductionmentioning
confidence: 89%
“…In the aleurone cells of barley, two types of vacuoles with different functions have been identified: one large, for protein storage; one small, with a similar function to that of lysosome (Swanson et al 1998). If large vacuoles in oat aleurone cells are homologous to those in barley, they express unfinished metabolism of aleurone grains related to the dehydratation of protein.…”
Section: Discussionmentioning
confidence: 99%
“…4C) which may correspond to small vacuoles (Fig. 4B, arrow) [34]. Thus, as stated by Swanson et al [34], BCECF may be capable of entering di¡erent vacuolar compartments.…”
Section: Glibenclamide Selectively Inhibits the Vacuolar Deposition Omentioning
confidence: 64%
“…In plants, evidence for vacuolar ABC-type transporters for £uorescent dyes was presented for LY [9]. Swanson et al [34] suggested the presence of a vacuolar ABC-type transport system for BCECF in bar- Fig. 5.…”
Section: Discussionmentioning
confidence: 99%